2009
DOI: 10.1007/s10165-009-0189-6
|View full text |Cite
|
Sign up to set email alerts
|

Is there evidence in support of the use of intra-articular hyaluronate in treating rheumatoid arthritis of the knee? A meta-analysis of the published literature

Abstract: Intra-articular hyaluronate (HA) injections for treating rheumatoid knee are still debatable, and this meta-analysis aims to elucidate the effectiveness of HA injection for rheumatoid knee. The meta-analysis comprised randomized clinical trials (RCTs) that compared the efficacy of HA injections with that of a placebo. The articles were retrieved after systematic searches of databases, including MEDLINE, EMBASE, and Japana Centra Revuo Medicina. The outcomes were classified into four categories: evaluation of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…One meta‐analysis assessed the efficacy of IA injections of HA in patients with RA [45] (1A+ Level). Data from 5 RCTs (720 RA patients) was pooled for meta‐analysis and the results indicated that IA HA is an effective and safe alternative therapy for the RA knee as it provided reliable pain reduction and reduction in inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…One meta‐analysis assessed the efficacy of IA injections of HA in patients with RA [45] (1A+ Level). Data from 5 RCTs (720 RA patients) was pooled for meta‐analysis and the results indicated that IA HA is an effective and safe alternative therapy for the RA knee as it provided reliable pain reduction and reduction in inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…Intra-articular injections of corticosteroids or hyaluronate are generally available for treating mono and oligoarthritis [14,15,30]. Although these treatments appear to be safe and beneficial, the reduction in pain and inflammation is only temporary.…”
Section: Discussionmentioning
confidence: 99%
“…Thus hyaluronate decoration of nanogels improved both selectivity and uptake of nanogels by the macrophages. Moreover, as intraarticular injection of hyaluronate has beneficial effects in patients with rheumatoid arthritis [38], the presence of hyaluronate at the surface of the nanogels in inflamed joints will not further enhance inflammation.…”
Section: Discussionmentioning
confidence: 99%